If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4)(7 + -1x) = x (7 * 4 + -1x * 4) = x (28 + -4x) = x Solving 28 + -4x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 28 + -4x + -1x = x + -1x Combine like terms: -4x + -1x = -5x 28 + -5x = x + -1x Combine like terms: x + -1x = 0 28 + -5x = 0 Add '-28' to each side of the equation. 28 + -28 + -5x = 0 + -28 Combine like terms: 28 + -28 = 0 0 + -5x = 0 + -28 -5x = 0 + -28 Combine like terms: 0 + -28 = -28 -5x = -28 Divide each side by '-5'. x = 5.6 Simplifying x = 5.6
| y^2-22y+24= | | 2x^2+8x-3=57 | | 2x(x+5)=110 | | 44+22x= | | 106=5x+(2x+8) | | 2c+4=-10 | | 180=(x+45)+x+x | | -148=4(8+8n)-2n | | 6f+15=-9 | | 4x+y=200 | | -148=-4(8+8n)-2n | | 4b+13+2b=16+3b+9 | | -11=(5+y) | | 12-7x=56 | | 4+8x= | | 21=2x+x+4x | | 3r-15=6 | | 5x+2.5=2x+40 | | .33x=4 | | 7c+2=-5 | | 2f+19=-27 | | 9-46= | | 5x-3y=-30 | | 9=3c-6 | | 0.64=In(y) | | 4r-16=28 | | 1x-6-2x+7x=30 | | 6=4x^2-10x | | 0.64=log(x) | | 3x^2+4x+36=0 | | 36n^2+49=36n | | 3a+8=8a-27 |